Análisis de las nuevas tecnologías de información y comunicación para determinar su influencia en las relaciones sociales, entre los jóvenes de bachillerato de la sección matutina de los colegios “Bernardo Valdivieso, Liceo de Loja y Pío Jaramillo Alvarado del cantón Loja, durante el periodo marzo-julio 2013. Propuesta alternativa - Teneda Jaramillo, Jorge Cristian (2014)
Communication as a medium between humans, since time immemorial , has been the one who has allowed through the exchange of messages between individuals get to create and generate knowledge . Communication involves the transmission of certain information. The communication process has not lagged behind in terms of technological advances, and goes hand in hand, constantly transforming, to be that important in the development of society tool. The information technology and communication are currently the most commonly used among young people and through them where they do much of the communication tool. The problem is that young people give priority to the use of these technologies to communicate with each other, rather than on communication on the physical plane. As a result of the surveys, it was determined that respondents do not spend time talking especially with your close family circle, parents, siblings, grandparents. KEYWORDS Technology, interpersonal communication, social communication, interpersonal relationships, social networks, today's youth